The Effect of Digital Literacy on Students’ Understanding of Professional Ethics in Accounting - Ningsi, Etty Harya; Utomo, Langgeng Prayitno; Kurniawan, Setia Budi; Safriliana, Retna; Assih, Prihat (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to examine the effect of digital literacy on students’ understanding of professional ethics in the field of accounting. As technological advancements increasingly shape the accounting profession, the ability to use digital tools responsibly has become essential for future accountants. This research employs a quantitative approach using a survey method, with data collected from accounting students at Battuta University. The sample was selected using purposive sampling, and responses were analyzed using multiple linear regression analysis. The results indicate that digital literacy has a significant positive effect on students’ understanding of professional ethics. Students with higher levels of digital competence tend to demonstrate greater awareness of ethical standards, particularly in the context of data integrity, digital communication, and responsible use of accounting software. The findings suggest the importance of integrating digital literacy development into accounting education curricula to strengthen ethical awareness in the digital era.